2017
DOI: 10.1371/journal.pone.0182848
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and mode of action of a novel analgesic β-toxin from the African spider Ceratogyrus darlingi

Abstract: Spider venoms are rich sources of peptidic ion channel modulators with important therapeutical potential. We screened a panel of 60 spider venoms to find modulators of ion channels involved in pain transmission. We isolated, synthesized and pharmacologically characterized Cd1a, a novel peptide from the venom of the spider Ceratogyrus darlingi. Cd1a reversibly paralysed sheep blowflies (PD50 of 1318 pmol/g) and inhibited human Cav2.2 (IC50 2.6 μM) but not Cav1.3 or Cav3.1 (IC50 > 30 μM) in fluorimetric assays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 55 publications
0
21
0
1
Order By: Relevance
“…This test has the advantages of being less invasive and more sensitive than neuropathic and inflammatory tests. Indeed, only a low amount of toxin candidate to be evaluated is necessary to relieve pain, as exemplified by GpTx-I, Cd1a, m3-HwTx-IV and Pn3a ( Deuis et al, 2016 ; Cardoso et al, 2017 ; Rahnama et al, 2017 ; Sousa et al, 2017 ). However, the question of lack of physiological relevance of this test may be raised.…”
Section: Analgesic Spider Toxins Targeting the Na V mentioning
confidence: 99%
“…This test has the advantages of being less invasive and more sensitive than neuropathic and inflammatory tests. Indeed, only a low amount of toxin candidate to be evaluated is necessary to relieve pain, as exemplified by GpTx-I, Cd1a, m3-HwTx-IV and Pn3a ( Deuis et al, 2016 ; Cardoso et al, 2017 ; Rahnama et al, 2017 ; Sousa et al, 2017 ). However, the question of lack of physiological relevance of this test may be raised.…”
Section: Analgesic Spider Toxins Targeting the Na V mentioning
confidence: 99%
“…Insecticidal activity was evaluated injection of peptides into the ventro-lateral thoracic region of sheep blowflies (Lucilia cuprina; mass 22.4-31.7 mg) as previously described [60].…”
Section: In Vivo Insecticidal Assaysmentioning
confidence: 99%
“…Cumulative inactivation [69]; b - [70]; c - [71]; d - [11,12]; e - [13]; f - [72]; g - [61]; h - [30,31]; i - [62]; j - [63] less prominent [19,38,39]. It has been suggested that all three putative interaction sites together form a G-protein binding pocket (GPBP) [40].…”
Section: Kinetics Of Current Activation/ Inactivationmentioning
confidence: 99%
“… a – [ 69 ]; b – [ 70 ]; c – [ 71 ]; d – [ 11 , 12 ]; e – [ 13 ]; f – [ 72 ]; g – [ 61 ]; h – [ 30 , 31 ]; i – [ 62 ]; j – [ 63 ] …”
Section: Introductionunclassified